PEMBUATAN SISTEM CATU DAYA DENGAN AUTOMATIC MAIN FAILURE UNTUK RUANG PERTEMUAN GEDUNG-71 - R.Enggar Timbul Santosa; Maradu Sibarani; Suripto Suripto; Rahmad Widodo (BATAN, 2012)
A CONSTRUCTION OF ELECTRICAL POWER SUPPLY FOR BUILDING-71 MEETING ROOM USING AUTOMATIC MAIN FAILURE SYSTEM. Electrical energy is used as the main support element of Building-71 Meeting Room service for mechanical systems, lighting, instrumentation systems and sound systems. An improvement of the reliability of electric power supply system in the meeting room is the purpose to be achieved. Automatic main failure (AMF) is a tool that serves to decrease downtime and improve reliability of electric power supply system. The method used is a combination of Automatic Transfer Switch (ATS) and Automatic main failure (AMF). The Ats-Amf system uses automatic controller module NB2 to start and stop generator system and change over the switch with two motorized Contactor as a medium of exchange source. The result is a power supply system with a safety alarm and safety trip to work quickly and precisely in order to avoid disruption to isolate the fatal damage. Combined of ATS and AMF system provides an integrated solution to automate in case of any failure with PLN. PEMBUATAN SISTEM CATU DAYA DENGAN AUTOMATIC MAIN FAILURE UNTUK RUANG PERTEMUAN GEDUNG-71. Energi listrik digunakan sebagai unsur penunjang utama pelayanan Ruang Pertemuan Gedung 71, baik untuk sistem mekanik, penerangan, maupun untuk sistem instrumentasi dan sound sistem. Meningkatkan keandalan sistem catu daya listrik di Ruang Pertemuan merupakan tujuan yang akan dicapai. Automatic main failure (AMF) merupakan alat yang berfungsi menurunkan downtime dan meningkatkan keandalan system catu daya listrik. Metode yang digunakan adalah gabungan antara Automatic Transfer Switch (ATS) dan Automatic main failure (AMF). Sistem Ats-Amf mempergunakan modul Automatic Controller NB2 yang berfungsi sebagai media start stop genset dan Change Over Switch motorized dengan dua buah Contactor sebagai media tukar sumber. Hasil yang diperoleh adalah sistem catu daya dengan pengaman alarm dan pengaman trip yang dapat bekerja cepat dan tepat dalam mengisolir gangguan agar tidak terjadi kerusakan yang fatal. Gabungan sistem ATS dan AMF memberikan solusi yang terpadu untuk mengotomatiskan dalam menangani masalah kegagalan PLN..